Numerical Investigation of Hydraulic Performance in Makhool Spillway Dam: 10.32526/ennrj/23/20240178 - Sadiq, Fatima A.; Hussein, Haitham A.; Zainol, Mohd R. Rozainy (Environment and Natural Resources Journal, 2025)
Dams are critical hydraulic structures, and analyzing their hydraulic properties is essential for ensuring their functionality. While experimental tests have traditionally been used to evaluate the performance of dams, but now (CFD) software, such as among this the Flow 3D, now offers a reliable alternative or complement to physical models, ensuring accuracy while reducing time and effort. This study investigates Makhools’ Spillway Dam in Iraq, one of the country’s most significant hydraulic projects. A 3D numerical model of the dam was developed to assess its operation and performance. Its properties were analyzed and validated by comparing the results with physical model data, focusing on key hydraulic parameters such as velocity and water flow depth. The velocity results closely align with the physical model data, with only a minor variation in flow depth, which remains within an acceptable range. The RMSE value for velocity was below 5%, while the difference in the flow depth was approximately 3.63%, indicating a strong correlation between the numerical and physical models. These findings confirm that advanced numerical modeling techniques can effectively complement or serve as a reliable alternative to real-world studies.